2006
DOI: 10.1530/rep.1.01038
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted gene expression in the rat embryo–fetal axis is altered in response to periconceptional maternal low protein diet

Abstract: In our previous study, we have shown that maternal low protein diet (LPD, 9% casein vs 18% casein control) fed exclusively during the rat preimplantation period (0-4.25 day postcoitum) induced low birth weight, altered postnatal growth and hypertension in a gender-specific manner. In this study, we investigated the effect of maternal LPD restricted only to the preimplantation period (switched diet) or provided throughout gestation on fetal growth and imprinted gene expression in blastocyst and fetal stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 62 publications
(73 reference statements)
3
97
2
Order By: Relevance
“…Maternal undernutrition also led to significantly lower levels of H19 (9.4%) and Igf2 (10.9%) mRNA in male, but not in female, fetal liver. These differences may result from the sex-specific programming of imprinted gene expression within the preimplantation embryo itself [40, 75,76]. Postnatal changes in cerebral chromatin conformation in rats born with IUGR are also sex-specific [26].…”
Section: Sexual Dimorphism In Consequences On Offspringmentioning
confidence: 99%
“…Maternal undernutrition also led to significantly lower levels of H19 (9.4%) and Igf2 (10.9%) mRNA in male, but not in female, fetal liver. These differences may result from the sex-specific programming of imprinted gene expression within the preimplantation embryo itself [40, 75,76]. Postnatal changes in cerebral chromatin conformation in rats born with IUGR are also sex-specific [26].…”
Section: Sexual Dimorphism In Consequences On Offspringmentioning
confidence: 99%
“…RNA was extracted from pools of 10-29 ovine blastocysts using Dynabeads mRNA DIRECT kit (Invitrogen Ltd; Kwong et al 2006). RT of mRNA from blastocysts was performed using QuantiTect RT kit (Qiagen Ltd), which eliminates genomic DNA and efficiently reverse transcribes small quantities of RNA in a two-step reaction.…”
Section: Transcript Analysismentioning
confidence: 99%
“…However, the functional significance of this is unclear as leukocyte methylation is notoriously variable and the studies did not examine any associated expression changes, effects on imprinting, or attempt any correlation with known phenotypic outcomes [43,44]. In a rat model of periimplantation low protein diet Kwong et al [36,37] demonstrated a male-specific reduction in birth weight and development of hypertension at a young age, associated with a 30% reduction in male blastocyst H19 expression. While methylation at the H19 DMR was slightly altered [37], it did not correlate with the observed change in expression, indicating that it was not mechanistically responsible and, although not directly tested, imprinting Neoplastic cell, Loss of imprinting (LOI) Slow cycling stem cell Relaxation of imprinting…”
Section: The Role Of Imprinted Genes In Developmental Plasticity In Rmentioning
confidence: 99%